ANALISIS DAMPAK EKSTENSIFIKASI BARANG KENA CUKAI PADA KANTONG PLASTIK TERHADAP PEREKONOMIAN INDONESIA - Muhammad Baidarus (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2018)
The use of plastic bags in Indonesia growing more rapidly because its characteristic that practical and steady. Ministry of Environment and Forestry stated the consumption of plastic bags that produced by 90 thousands modern retail outlets in 2016 reaches 9,85 billion. The high rate consumption of plastic bags made Indonesia as the second biggest country produced plastic rubbish after China. As a result, it bring about uncontrollable environmental pollution that harmful to health. This research study the effects of excise in the economy. The establishment of excise on plastic bags cause the plastic bag prices more increasing. Each 1% increase of plastic bag price decrease the demand in the amount of 0,957% and the 20% excise tariff is potentially increase excise revenue to IDR1.603.268,19 million. Therefore, the establishment of excise on plastic bags is the right way that must be applied by goverment to reduce the high cosumption of plastic bags in Indonesia. This research use a descriptive method by studying the result of scientific analytical of data that obtained from documentary and interview result.